(untitled) (International Journal of Physiotherapy, 2016)
Background: Cervical radiculopathy occurs annually in 85 out of 100,000 people. It is very disabling and interferes with the ADL of the patients. Many studies had shown the effectiveness of neural mobilization and TENS in reduction of pain and disability in patients with cervical Radiculopathy. But there are less documented studies that had shown the combined effect of neural mobilization and TENS and effectiveness of both over only neural mobilization in patients with cervical radiculopathy. Methods: 30 male and female subjects were assessed as cervical radiculopathy and selected for the study. This includes unilateral cervical radiculopathy. They were categorized randomly into two groups as group receiving neural mobilization and TENS (experimental group I) and group receiving only neural mobilization (experimental group II) with 15 patients in each group. Assessment was taken using VAS and NDI prior to treatment. Treatment was continued for 14 days and at the end of 14 days patients were reassessed using the same scales. Results: Group 1 receiving both the treatments had shown more significant reduction in pain and disability compared to Group 2 receiving only neural mobilization after 14 days of treatment. Conclusion: Both neural mobilization and TENS are effective in reduction of pain and disability in patients with cervical radiculopathy. And when compared, combined treatment is more effective than only neural mobilization.